2020
DOI: 10.3390/nu12020420
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Maternal Mediterranean Diet in Pregnancy on Insulin Resistance is Moderated by Maternal Negative Affect

Abstract: There is inconsistent evidence that healthy dietary interventions can effectively mitigate the risk of adverse outcomes associated with elevated insulin resistance in pregnancy, suggesting that other moderating factors may be at play. Maternal psychological state is an important factor to consider in this regard, because stress/mood state can directly influence glycemia and a bidirectional relationship may exist between nutrition and psychological state. The objective of this study was to examine the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 60 publications
(66 reference statements)
0
46
0
1
Order By: Relevance
“…Recent studies have shown that diets with a higher intake of fruits, vegetables, pulses, and fish lead to positive outcomes during pregnancy [ 18 , 19 ]. Generally speaking, greater adherence to the Mediterranean diet during pregnancy can protect against excessive cardiometabolic risk for offspring [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that diets with a higher intake of fruits, vegetables, pulses, and fish lead to positive outcomes during pregnancy [ 18 , 19 ]. Generally speaking, greater adherence to the Mediterranean diet during pregnancy can protect against excessive cardiometabolic risk for offspring [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 27 observational studies were included in the review: 17 (63.0%) cohort studies [20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; 7 (25.9%) cross-sectional studies [38][39][40][41][42][43][44]; 2 (7.4%) case-control studies [23,45]; and, 1 (3.7%) nested case-control study [46]. Table 2 provides a summary of the key characteristics of these 27 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All studies included fruits as a beneficial component in their index . Seven studies specified the inclusion of fruit juices in the fruit component [20,33,[40][41][42]44,46]. Only one study explicitly excluded fruit juices from inclusion in the fruit component of their index [22].…”
Section: Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Es existieren zahlreiche nichtdiätetische Modifikatoren dieser Assoziation. Lindsay et al fanden beispielsweise keine Assoziation zwischen MD und Insulinresistenz, aber sie be-richteten von einer Kombination psychologischer Faktoren wie Ängstlichkeit, Trauer, Wut und Stress als möglichem abmildernden Faktor der Assoziation zwischen mütterlicher MD und Insulinresistenz (HOMA-IR)[16].Der BMI ist zusätzlich mit unterschiedlichen Verhältnissen der Fettsäurenzusammensetzung der Muttermilch assoziiert, was wiederum die Gewichtszunahme des Säuglings in den ersten Lebensmonaten beeinflussen könnte[17].…”
unclassified